Kontektualitas Nilai-Nilai Ke-Islaman dalam Sistem Kewarisan: Kajian Modernitas Agama tentang Keadilan dan Pembagian Harta Tinjauan Sosiologi: Penelitian - Antoni Yoseph; Jumni Nelli (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study explores the relationship between Islam and modernity by tracing the dynamics of tradition and innovation emerging in various aspects of social, cultural, and intellectual life. In an era of rapid globalization, Muslims face the challenge of maintaining their traditional values ​​while responding to changes involving technology, politics, and economics. The findings indicate efforts to reinterpret religious texts, establish new institutions, and adopt modern technologies that remain in line with Islamic values. This article emphasizes the importance of an adaptive and inclusive approach to bridging tradition and innovation, so that Muslim communities can contribute to the formation of a more harmonious global order without losing their religious identity. In this context, Islamic inheritance law also serves as an important arena for re-reading and adaptation amidst modern social dynamics. From a sociological perspective, inheritance law is understood not only as a normative rule governing the distribution of inherited property but also as a reflection of the social structure, gender relations, and distribution of economic power in Muslim societies. Transformations in family patterns, the increasing participation of women in the public sphere, and changes in the economic system have given rise to demands for a reexamination of inheritance practices to ensure they remain in line with the principles of social justice without abandoning their sharia foundations.